Cooperative learning in process dynamics & control course for undergraduate chemical engineering students - Mohd. Yusof, Khairiyah; Harun, Jamaludin; Abu, Mohd. Salleh (2004)
titute in the country, Universiti Teknologi Malaysia (UTM) is aggressively encouraging teaching staff to enhance teaching and learning to produce graduates who are relevant in today’s highly competitive world. To achieve this goal, grassroots awareness and training campaign, followed by encouragements are rigorously made. Active learning techniques, especially the Cooperative Learning (CL) and Problem Based Learning (PBL) are currently being promoted across all disciplines as well as levels of studies. This effort which was initiated by a group of enthusiastic teaching staff received a welcome endorsement from the highest level of university administrative key personnel. A special task force called CL-PBL Support Group was then set up to facilitate the promotion of CL and PBL practices across the board. At implementation level, faculty-based core groups were set up and trained to acquire and apply the necessary knowledge and teaching skills pertaining to these active learning approaches. This paper describes strategies and efforts to convince and encourage the implementation of active learning techniques among teaching staff and administrators, especially those in the engineering and engineering-related faculties. Training and support provided to academic staff are also discussed. Finally, factors that influence the success of university-wide implementation will be included.